استراتيجية التناص في روايات الهاشمي سعيداني - بن حركات, الجمعي (University of Eloued جامعة الوادي, 2015)
قمت بدراسة قضية نقدية حساسة تتمثل في "التنا ص"، وبينت كيف استفاد الروائي "الهاشمي سعيدان ي" من هذا الزخم الروائي المكت وب بالعربي ة، وقد وجد الطريق معبد ا، وممهدا من طرف الروائيي ن، الذين سبقوه، ولقد استحوذ على هذه الفسيفساء، ونظمها وفق كيميائيته الخاصة، وهذا يعود إلى ذاكرة الروائي التي اختزنت الأحداث، والأوضاع المبثوثة في روايات الأدباء الجزائريين، وجعلها تتلاءم مع رؤيته الجديدة للواقع الجزائري وللتاريخ، فكانت استراتيجية "التناص" لاستحضار النصوص السابقة وامتصاصها، وتجاوزها نحو جماليات جديدة، وكتابة متميزة، فتولد "تناص". I studied a sensitive critical issue, which is the “intertextuality”, and showed how the novelist “HachemiSaidani” benefited from the momentum of novels written in Arabic. He found the road paved by the novelists who preceded him and he engrossed this mosaic and organized it according to his own chemistry. This goes back the novelist memory that stored the events and the situations portrayed in the novels of Algerian writers and make them fit in with his new vision of Algerian reality and history. Therefore, the intertextuality strategy was to evoke the previous texts and overcome them toward new aesthetics and excellent writings giving birth to “intertextuality”.
Keywords: الهاشمي سعيداني، التناص، الرواية; Hachemi Saidani, intertextuality, the novel